Biodiversity of the projected Nivetsky Reserve (Vyshhorodsky district, Kyiv Region) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Questions: Is the biodiversity of a part of the territory of Northern Polissia near the Uzh River suitable for the establishment of a new Nivetsky Reserve? Locations: Kyiv Region. Methods: field research, critical analysis of the literature sources and electronic resources. Nomenclature: lichens follow Kondratyuk et al. (2021), non lichenized fungi follow Index fungorum (2023), mosses follow Boiko (2014), vascular plants follow POWO (2023) Results: The publication considers an important biodiversity area of 473 hectares in the vicinity of Cheremoshna and Nivetske villages in the Vyshhorod district of Kyiv region, which is proposed to be designated as a landscape reserve of national importance with the name "Nivetsky". There are 23 species of fungi, 22 species of lichens, 7 species of bryophytes and 264 species of higher vascular plants that have been revealed in the projected reserve. Among the rare plant species, four are listed in the Red Data Book, 15 are regionally rare for Kyiv region, and 2 are included in the Appendix I of Resolution 6 of the Bern Convention. One species of fungi is included in the Red Data Book. Among animals, even according to preliminary studies, 13 species are listed in the Red Data Book of Ukraine and 12 in the Resolution 6 of the Bern Convention (2 species are included in both lists simultaneously). In addition to the list of rare species, a list of habitats from the Resolution 4 of the Bern Convention which were found on the territory of the projected reserve is provided (18 types in total). Habitat types that are protected at the European level, in particular D5.2, G1.51, and especially G1.8, comprise a significant part of the reserve area. Conclusions: Thus, this area has a high habitat and biotic diversity. The most valuable areas for conservation are old-growth oak forests and subboreal forests, mesotrophic and eutrophic bogs. The list of species known for the projected Nivetsky Reserve is published for the first time.
Keywords: rare species, rare habitats, Forest zone, Kyiv region, Resolution 4 of the Bern Convention.